Would You Trust a Diagnostic Procedure with 100% Specificity and 96% Sensitivity? - Eeckhaut, Lisa Van den; Lemper, Jean-Claude; Rebel, Sonja; Schils, Michiel; Barbé, Kurt; Pierard, Denis; Amstutz, Raphael; Beyer, Ingo (Archives of Clinical and Medical Case Reports, 2020)
Nasopharyngeal swab (NPS) RT-PCR SARS-CoV-2 detection has approximately 100% specificity and 70% sensitivity. We report a case of a 94-year-old patient without significant comorbidities, who developed respiratory symptoms 7 days after being transferred for wrist-fracture rehabilitation. NPS RT-PCR for SARS-CoV-2 was negative on day 1, 7, 12 and 19 after symptom onset. No other viral or bacterial pathogens were detected, nor was there improvement with different empirical antibiotics. CT showed non-specific five-lobe involvement. She slowly recovered clinically and radiologically. SARS-CoV-2 antibody testing became available in Belgium, revealing specific IgG in this patient. Despite serial testing and a cumulative sensitivity of 96%, COVID-19 could not be detected through NPS. This underlines the precaution that should be taken in interpreting a negative test result when the clinical suspicion is high, as well as the need for detailed information about pre- and post-test probabilities in different settings. <gdiv></gdiv>